An Analysis of Eighth-Grade Students’ of Mathematical Reasoning Ability in Statistics Based on Independent Learning Methods - Cut Morina Zubainur; Cut Khairunnisak; Nurul Akmal; ibrahim Ibrahim; Aiza Rafsanjani (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
The purpose of this study is to describe the level of mathematical reasoning ability in statistics material viewed from the learning independence of class VIII students of SMP Negeri 6 Banda Aceh City. This study is a qualitative study with a descriptive type. The subjects in this study were 22 class VIII / 1 students of SMP Negeri 6 Banda Aceh City. The instruments in this study consisted of questionnaires, test questions and interview guidelines. The results of the study show (a) Students with a high learning independence category fulfill the five indicators of mathematical reasoning ability. (b) Students with a moderate learning independence category, were only able to work on two of the four questions given and from two of the questions the students were able to fulfill the five indicators of mathematical reasoning ability. (c) Students with a low learning independence category, were only able to work on one of the four questions given and from one question the students were only able to fulfill the first indicator, namely providing a mathematical statement. The mathematical reasoning ability of students reviewed from learning independence obtained the following results; a) students who have a high level of learning independence have high category mathematical reasoning abilities, b) students who have medium and low levels of learning independence have low category mathematical reasoning abilities.